Pemanfaatan Limbah Kertas (Pulp) dan Serat Batang Pisang Menjadi Campuran Bahan Pembuatan Asbes Plafon Ramah Lingkungan - Reyhan Fajrul Arsal; Muchammad David Rivaldy; Hartono Hartono; Shifa Fauziyah (Universitas Diponegoro, 2024)
Garbage waste in Indonesia is classified as many, including organic and inorganic. Therefore, research was carried out with the aim of utilizing waste paper and banana tree trunks as a mixture for making environmentally friendly asbestos ceilings. The method used is an experimental method, with a mixture of cement and sand composition of 1:2 namely AP0 (38%, 60%, 2%) ; as well as variations in the composition of the mixture of cement, paper pulp, and banana stem fiber used, among others: AP1 (39%, 60%, 2%) ; AP2 (44%, 55%, 2%) ; AP3 (48%, 50%, 2%) ; AP4 (53%, 45%, 2%) and the various compositions used for mixing cement, paper pulp, banana stem fiber, and sand include: AP5 (39%, 20%, 1%, 40%) ; AP6 (44%, 20%, 1%, 35%) ; AP7 (48%, 20%, 2%, 30%) ; AP8 (53%, 20%, 2%, 25%). The highest average flexural strength results for the variation without sand in the AP4 sample = 68.121 kgf/cm2, while the variation using sand in the AP8 sample = 70.358 kgf/cm2. For the water absorption test results, the lowest average variation without sand was in the AP4 sample = 18.36%, while the variation using sand in the AP8 sample = 12.20%. This test includes flexural strength and water absorption. The use of paper pulp can reduce flexural strength and increase water absorption while banana stem fiber increases flexural strength and decreases water absorption. Therefore, it can be concluded that asbestos ceilings with a mixture of pulp and banana stem fiber are better, economical, and lighter than conventional asbestos ceilings and still meet SNI.